2018
DOI: 10.1111/jnu.12441
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Work Environment and Suicidal Ideation Among Nurses in Taiwan

Abstract: Purpose Nurses are exposed to a poor psychological work environment; this may cause poor mental health, which is a risk factor for suicidal ideation. We investigated the association between psychological work environment and suicidal ideation among hospital nurses in Taiwan. Design We conducted a cross‐sectional survey in Taiwan female nurses using stratified sampling by region (north, central, south, and east) to select representative centers for this study. Methods A self‐report questionnaire including items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…In addition, our result was similar to the burnout levels of 73.1% to 86.9% reported by oncology nurses in China [ 35 ] and by intensive care unit nurses in Argentina [ 36 ]. As burnout has been reported to be significantly associated with mental problems such as depression and job dissatisfaction [ 21 , 37 ], active strategies are required to accurately assess nurses’ burnout. In particular, organizational and interpersonal resources have been shown to play an important role in reducing exhaustion in clinical nurses [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our result was similar to the burnout levels of 73.1% to 86.9% reported by oncology nurses in China [ 35 ] and by intensive care unit nurses in Argentina [ 36 ]. As burnout has been reported to be significantly associated with mental problems such as depression and job dissatisfaction [ 21 , 37 ], active strategies are required to accurately assess nurses’ burnout. In particular, organizational and interpersonal resources have been shown to play an important role in reducing exhaustion in clinical nurses [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient job control (OR: 2.215, 95% CI: 1.017–4.736) and lack of reward (OR: 2.236, 95% CI: 1.021–5.153) are associated with suicidal ideation among Korean subway drivers [ 18 ]. Job stress (OR: 2.7, 95% CI: 2.2–3.3), personal burnout (OR: 3.8, 95% CI: 3.1–4.6), and client-related burnout (OR 3.9, 95% CI: 3.1–5.0) are associated with suicidal ideation in Taiwanese female nurses [ 19 ]. Among work-related factors, a recent degrading experience or harassment at work (OR 2.83, 95% CI: 1.13–7.09) is related to recent suicidal ideation in Swedish surgeons [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient job control and lack of reward correlated with increased suicidal ideation among Korean subway drivers [ 18 ]. Job stress correlated with increased suicidal ideation in Taiwanese female nurses [ 19 ]. A recent degrading experience or harassment at work correlated with recent suicidal ideation in Swedish surgeons [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, a study supports the relationship between long work hours and suicidal ideation [16]. Another study found the association between work burnout and suicidal ideation among nurses [17]. The relationship between jor stress and suicidal ideation is also identified in Chinese county-level hospitals [18].…”
Section: Introductionmentioning
confidence: 85%